고온벽과 충돌하는 나노유체 액적 거동에 관한 연구 - 김으뜸; E. Dd. Kim; 박인한; I. H. Park; 배녹호; N. H. Bae; 강보선; B. S. Kang (한국분무공학회지, 2015)
In this study, the behavior of water or nanofluid droplets impacting upon a hot surface was investigated by visualization of impacting phenomena with time-delayed photographic technique. Changing the mass ratio of nanofluid and the temperature of the heated surface, the characteristics of the spreading behavior and the diameter of spreading liquid film was compared between water and nanofluid droplets. The impacting droplet spreaded as a liquid film after impact and nanofluid droplets spreaded more widely than water droplets. After reaching the maximum diameter, water droplets shrinked more than nanof- luid droplets. Based on this, the heat transfer area from a hot surface to impacting nanofluid droplets would be wider than that of impacting water droplets. Considering individual impacting droplet only, spray cooling using nanofluid would be better than using water.